Understanding the Role of Simulation-Based Mathematics Learning Media in Developing Early Childhood Cognitive Abilities - Ruly Eko Setiawan; Samuel Karim (Delta-Phi: Jurnal Pendidikan Matematika, 2025)
This study aims to understand the role of simulation-based mathematics learning media in developing the cognitive abilities of early childhood. This media is an interactive approach that utilizes a digital or virtual environment to represent mathematical concepts in a concrete and engaging manner for children. Through simulation, children can explore, manipulate, and solve mathematical problems directly, thereby encouraging active engagement and meaningful learning. Recent studies have shown that the use of simulation media can improve conceptual understanding, critical thinking skills, and problem-solving abilities in early childhood. Simulation also provides an adaptive learning experience that can be tailored to the needs and learning styles of each child, effectively accommodating the diversity of cognitive abilities in the classroom. In addition, simulation media supports cognitive development in accordance with Piaget's and Vygotsky's theories, where children learn through active interaction with the environment and guidance from adults. This study highlights the importance of selecting and developing simulation media that are appropriate to the cognitive developmental stage of early childhood, as well as the need to evaluate the effectiveness of these media through valid and reliable measuring instruments. Thus, simulation-based mathematics learning media has the potential to be an innovative solution in improving the quality of mathematics learning and supporting the optimal cognitive development of early childhood.